2002
DOI: 10.1038/sj.leu.2402709
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of Hox11L2 expression in children with T-ALL

Abstract: The orphan homeobox gene HOX11L2 was previously found to be transcriptionally activated as a result of the t(5;14)(q35;q32) translocation in three T-ALL cases. We now tested by RT-PCR Hox11L2 expression in 23 consecutive cases of T-ALL (15 children aged 0.8-14 years, eight adults aged 17-55 years) and as control 13 B-ALL patients from a single institution. Hox11L2 expression was undetectable in all patients with B-ALL, nor in adults with T-ALL. Nine children (60% of the cases), all boys, expressed Hox11L2. Bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 27 publications
(30 reference statements)
2
30
0
Order By: Relevance
“…Our data support the hypothesis that HOX11 deregulation is associated with a uniform cortical thymocyte stage of maturation arrest. 9,18 Such a maturation arrest is observed in pediatric as well as adult patients and is independent of the patients' age. In contrast, our study results confirm an age dependency of HOX11 expression and show a higher incidence of HOX11 expression in adults than in children.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 96%
See 2 more Smart Citations
“…Our data support the hypothesis that HOX11 deregulation is associated with a uniform cortical thymocyte stage of maturation arrest. 9,18 Such a maturation arrest is observed in pediatric as well as adult patients and is independent of the patients' age. In contrast, our study results confirm an age dependency of HOX11 expression and show a higher incidence of HOX11 expression in adults than in children.…”
Section: Hox11l2-positive Thymic T-all With Reduced Outcomementioning
confidence: 96%
“…In adolescents it has been found in around 16% and is further declining to 11% in T-ALL patients older than 20 years. [8][9][10]18,19 Reports on the FRALLE protocol with 6 HOX11L2-positive of 28 patients and the Total Therapy studies XI-XIII with 6 HOX11L2-positive of 59 patients revealed a negative prognostic impact of HOX11L2 expression. 6,7 Confirmed were these reports by an …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the t(10;14) translocation is seen in only 4-7% of reported T-ALL cases, a recent study revealed elevated HOX11 expression levels in leukemic blasts in B50% (37/76) of pediatric T-ALL cases (Kees et al, 2003). Moreover, an additional 30% of pediatric T-ALLs exhibited inappropriate activation of the related HOX11 gene, HOX11L2 (Mauvieux et al, 2002). Clinically, patients with HOX11-positive lymphoblasts have a better prognosis when treated with modern combination chemotherapy than patients with T-ALLs involving activation of HOX11L2 (Ferrando et al, 2002(Ferrando et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%
“…Ectopic HOX11L2 expression can also be found in T-ALL without a 5q35 translocation by RT-PCR analysis. 19,130 HOX11L2 is a member of the homeobox-containing protein family. 131 Overexpression of HOX11L2 has been shown to correlate with a poor prognosis.…”
Section: Translocations Involving the Ranbp17 And Tlx3 (Hox11l2) Regimentioning
confidence: 99%